Cognition in Patients With Memory Difficulties and Dementia Relative to APOE e4 Status - Hestad, Knut; Engedal, Knut; Horndalsveen, Peter; Strand, Bjørn Heine (Frontiers in Psychology, 2021)
The aim of this study was to investigate whether cognitive performance was equally influenced by Apolipoprotein E (APOE, with its three alleles, e2, e3 and e4) in patients with subjective cognitive decline (SCD), mild cognitive impairment (MCI), and Alzheimer’s disease (AD). In addition, we examined two reference groups, one with a combination of Vascular dementia (VaD) and AD (VaD/AD) and one with a combination of diffuse Lewy body’s disease (DLB) and Parkinson’s disease dementia (PDD) (DLB/PDD) to examine whether the APOE e4 allele influenced cognition in these patients in the same way. Our study comprised data from 2,113 patients (51% women), with a mean age of 71.0 years (SD 10.6) and 12.1 years of education (SD 3.8). Of them, 953 (55%) had at least one APOE e4 allele; 912 (43%) had one and 248 (12%) had two e4 alleles. Three neurocognitive tests were used to measure cognition: the Mini Mental State Examination (MMSE), the 10-word test of the Consortium to Establish a Registry for Alzheimer’s Disease Word List (CERAD-WL) (immediate and delayed recall), and the Trail Making Test Part A. The APOE genotypes were regressed against cognitive function using linear regression, adjusting for diagnosis, age, sex, and education. The interaction diagnosis*APOE was investigated. The allele type had the largest effect on cognitive performance assessed by the CERAD-WL delayed recall test, less for the other tests. Those without the e4 type scored 1.2 units better than those with e4 allele(s) (p<0.001). Furthermore, there was a significant inverse dose-response pattern between number of e4 alleles and cognitive performance; those with one allele scored 0.43 units better than did those with two alleles (p=0.003), and those without e4 scored 0.63 units better than those with one e4 (p<0.001). This pattern did not differ between the five diagnostic groups studied.